1963
DOI: 10.1002/cber.19630960111
|View full text |Cite
|
Sign up to set email alerts
|

Über eine neue Ringschlußreaktion aromatischer Diazoamino‐verbindungen und zur Kenntnis von 1.2.3‐Triazolinen

Abstract: Diazoaminoverbindungen aus aromatischen Diazoniumverbindungen und Diathanolamin-dischwefelsaureester schlieDen in natriumcarbonatalkalischer L8sung unter Abspaltung einer Schwefelsaureestergruppe einen 1.3-disubstituierten 1.2.3-Triazolinring. Das neue Ringsystem ist in saurer LBsung bestandig, unter Einwirkung von Atzalkalien wird es zersetzt. Bei der katalytischen Hydrierung entstehen unter Ammoniakabspaltung N-Aryl-N'-[P-hydroxy-athyll-athylendiamine.Die Triazenbildung aus aromatischen Diazoniumverbindungen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Indeed, we have been able to use this operationally simple two-step procedure to prepare a variety of 1,2-diamines 7 stereoselectively and in reasonable yield (Table ). Significantly, we have found that the hydrogenation of 6 to 7 requires only 1 atm of H 2 , not 50–60 atm as reported by Mohr and Hertel . We simply use a party balloon to supply the necessary H 2 .…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Indeed, we have been able to use this operationally simple two-step procedure to prepare a variety of 1,2-diamines 7 stereoselectively and in reasonable yield (Table ). Significantly, we have found that the hydrogenation of 6 to 7 requires only 1 atm of H 2 , not 50–60 atm as reported by Mohr and Hertel . We simply use a party balloon to supply the necessary H 2 .…”
supporting
confidence: 57%
“…In 1963, Mohr and Hertel reported that hydrogenation of 1,2,3-triazolinium ions, 1 , under 50–60 atm of H 2 over Raney Ni excised the central N atom, providing the corresponding 1,2-diamines, 2 , in good yield (Scheme ). This report gave us confidence that if we could convert alkenes to 1,2,3-triazolinium ions, we could use hydrogenation over Raney Ni to excise their middle N atoms and provide a 1,2-diamine.…”
mentioning
confidence: 91%
“…High yields of 1-vinyl-1,2,3-triazole [15] , and 1-isopropyl-1,2,3-triazole [16] have been reported, however the use of expensive 1(H)-1,2,3-triazole is required. Previously, preparations of 1,3-di-substituted-1,2,3-triazolium salts have been reported using various alkylating agents and 1-alkyl substituted 1,2,3-triazoles [17][18][19][20][21], also by reactions of 1,3-diaza-2-azoniallene salts with alkynes [22,23].…”
mentioning
confidence: 99%